Cool coating performance for urban heat island (UHI) mitigation in residential area – numerical study - Tan, Sharon Hui Shan (Nanyang Technological University, 2021)
With an increasing population and limited land space, the population density in Singapore is among the highest in the world. It correspondingly resulted in a very high housing density as well. This high population and building density situation contribute to the Urban Heat Island (UHI) effect in Singapore. The average temperature in urban areas of Singapore is 1 ⁰C to 2 ⁰C higher than the average temperature in the surrounding rural areas. The UHI effect has serious consequences such as more heat-related illnesses and air pollution. Since Singapore has a hot and humid climate, the UHI effect is magnified further whereby it negatively affects the health of all the people living in Singapore. In Singapore’s government efforts to build a sustainable country, a pilot test is conducted to test the effectiveness of cool paint in reducing the ambient temperature of the residential areas. The objective is to evaluate the effectiveness of cool paint using a 3D microclimate model, ENVI-met. Simulation results from ENVI-met were validated with the observation from the experimental study. From the simulation in October 2020, cool paint is effective in mitigating the UHI effect by reducing air and surface temperature. The air temperature on the carpark, facade and roof is reduced by an average of 1.1 ⁰C, 0.7 ⁰C and 1.4 ⁰C, respectively with cool paint. The surface temperature on the carpark driveway, facade and roof is reduced by an average of 6.3 ⁰C, 3.6 ⁰C and 12.5 ⁰C, respectively with cool paint. The temperature on the top-floor ceiling and indoor wall surface is reduced by an average of 6.0 ⁰C and 2.6 ⁰C, respectively with cool paint. For the outdoor thermal comfort, from 9 am to 4 pm, the average improvement in PMV at 1.5 m above ground level is 0.6, the cool paint slightly improves the outdoor thermal comfort but generally the outdoor thermal comfort is in the hot category.